Early childhood interactive education media: Penguinplayground edu - Sim, Jing Jing (2025)
This study presents a comprehensive mobile application multimedia kindergarten learning platform that integrates digital technologies into the educational domain. The platform utilizes the immersive potential of multimedia and mobile applications to create a dynamic and engaging learning environment specifically for kindergarten-aged children. The main motivation behind the platform is the urgent need to bridge the gap between traditional pedagogy and the vast potential offered by digital advancements. Furthermore, this study aims to address the inherent shortcomings of current multimedia kindergarten learning platforms. By integrating interactive multimedia content, the platform facilitates rich educational journeys that inspire curiosity, creativity and personalized learning experiences. The platform works to redefine the way children interact with educational resources, providing accessibility, adaptability, and engagement in a variety of learning environments. Overall, this research has pioneered a transformative approach to early childhood education that promotes a holistic and engaging learning experience. By combining cutting-edge technology with pedagogical expertise, the Multimedia Kindergarten Learning Platform for Online/Offline/Mobile Applications aims to empower parents, educators and early childhood learners, ultimately shaping the future of early childhood education.